2012
DOI: 10.1103/physreve.86.041602
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field-induced interfacial instabilities of a soft elastic membrane confined between viscous layers

Abstract: We explore the electric-field-induced interfacial instabilities of a trilayer composed of a thin elastic film confined between two viscous layers. A linear stability analysis (LSA) is performed to uncover the growth rate and length scale of the different unstable modes. Application of a normal external electric field on such a configuration can deform the two coupled elastic-viscous interfaces either by an in-phase bending or an antiphase squeezing mode. The bending mode has a long-wave nature, and is present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 98 publications
(128 reference statements)
0
13
0
Order By: Relevance
“…The accuracy of the LSA performed for the simplified LPL model has been verified in the asymptotic limits in Figure . The solid and the broken line in this figure show the variation in the growth rate (ω) with the wavenumber ( k ) plot for two different unstable modes of the existing study on the PPP trilayer . The circular symbols indicate that the LSA discussed in the present work can reproduce these unstable modes in the limit with zero conductivities at the liquid layers (σ 1 = σ 3 = 0) together with zero surface charge densities at the interface ( q 10 = q 20 = 0).…”
Section: Linear Stability Analysismentioning
confidence: 77%
See 4 more Smart Citations
“…The accuracy of the LSA performed for the simplified LPL model has been verified in the asymptotic limits in Figure . The solid and the broken line in this figure show the variation in the growth rate (ω) with the wavenumber ( k ) plot for two different unstable modes of the existing study on the PPP trilayer . The circular symbols indicate that the LSA discussed in the present work can reproduce these unstable modes in the limit with zero conductivities at the liquid layers (σ 1 = σ 3 = 0) together with zero surface charge densities at the interface ( q 10 = q 20 = 0).…”
Section: Linear Stability Analysismentioning
confidence: 77%
“…A previous study showed that the interfaces of a purely dielectric trilayer can readily deform into a bending mode when exposed to a small destabilizing electric field . In comparison, threshold field intensity is essential to initiate the squeezing mode of instability.…”
Section: Results and Discussionmentioning
confidence: 98%
See 3 more Smart Citations